Scientific Study of Sociological Problem: Solve the Begging & Poverty Problem in Iraq - Alfahham, Muayad Baqer Mohammed; Kadhium, Afaq Jaber; Hussein, Hanan Ali; Mohammed, Jalal Hasan; Almosawy, Manar Ghyath Abd Almutalib; Aljamali, Nagham Mahmood (International Journal of Islamic Business & Management, 2020)
This Case study to Solve social problem like The begging in street and poverty problem for small cities., This study investigated the prevalence and consequences of street begging among adults and children in small towns, Descriptive of this scientific study was adopted for the many cases in many small and poor towns and Finding solutions Of The Begging Problem : Name Problem: Treatment of Social problem (The Begging) Type of Study: Scientific Study for Treatment of Social Problem (The Begging) Aim of Scientific Study: Finding solutions of The Begging Problem